PENGARUH MODEL QUANTUM LEARNING TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS X AKUNTANSI SMK NEGERI 2 KOTA JAMBI - Abdoel Gafar; Agustina Aritonang (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research aims to describe the impact of of quantum learning model towards students ability in writing poetry at class X of accounting major SMK Negeri 2 Jambi City school year 2018/2019. The design of this research uses quasi experiment with a quantitative approach. Sampling was carried out using the purposive sampling technique of the X-grade students of SMK Negeri 2 Jambi City. It is obtained that class X of accounting 2 as the experimental class and class X of accounting 3 as the control class. The research results show that the average score of the experimental is 80.42 and the average score of control class is 74. After testing the normality test, the experimental class sig score is 0.170 > 0.05 and the control class sig score is 178 > 0.05 (significance level). Thus it can be concluded that the data of the two classes is fall intro category of normal distribution. From the homogeneity test, it is obtained that sig score is 0.462 > of a significant level (α = 0.05) Thus it can be concluded that both classes have the same or homogeneous variants. Hypothesis testing uses SPSS 20 applications. T test of two independent samples shows that SIG T count 0,043 < 0.05 then Ho is rejected Ha is received. So, the results of students ability in writing poetry at class X of Accounting at SMK Negeri 2 Jambi city that use quantum learning model is better than the learning outcomes of students who use conventional learning.